A Population-Based Study of Social Demographic Factors, Associated Diseases and Recurrent Corneal Erosion in Taiwan - Jan, Ren-Long; Ho, Chung-Han; Wang, Jhi-Joung; Tseng, Sung-Huei; Chang, Yuh-Shin (Frontiers in Public Health, 2022)
Purpose: To investigate the association of recurrent corneal erosion (RCE) with sociodemographic factors and associated ocular conditions or systemic diseases. Methods: This nationwide, population-based, retrospective, matched case-controlled study included 98,895 newly diagnosed RCE patients, identified by the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) code 361.42, were selected from the Taiwan National Health Insurance Research Database. The age-, sex-, and index date- matched control group included 98,895 non-RCE control group also selected from the Taiwan Longitudinal Health Insurance Database 2000. Sociodemographic factors and associated ocular conditions or systemic diseases were examined using univariate logistic regression analyses, and continuous variables were analysed using paired t-test. The odds ratio (OR) of developing RCE were compared using adjusted logistic regression analysis. Results: Patients with ocular conditions including corneal abrasion, ocular allergic conditions, and corneal dystrophy were more likely to have RCE than the control group (adjusted OR=63.56, 95% CI=42.06–96.06, p<0.0001; adjusted OR=24.27, 95% CI=20.51–28.72, p<0.0001; adjusted OR=17.10, 95% CI=5.14–59.93, p<0.0001, respectively). Patients with systemic diseases such as diabetes mellitus, hyperlipidaemia, and atopy trait have significantly higher ORs for RCE development. Patients residing in either Northern Taiwan or a metropolis city had higher odds of developing RCE; however, there were no significant differences in income or occupation on the probability to develop RCE. Conclusions: RCE is strongly associated with corneal abrasion, ocular allergic conditions, corneal dystrophy, diabetes mellitus, hyperlipidaemia, and atopy trait.